2018
DOI: 10.1155/2018/1782847
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Macular Hole Closure after Valsalva Retinopathy and Nd:YAG Laser Treatment

Abstract: Purpose The purpose of this report is to present a case who had spontaneous macular hole closure after Nd:YAG laser membranotomy applied to premacular haemorrhage associated with Valsalva retinopathy. Methods Case report. Results A 19-year-old young male patient presented to our clinic with sudden vision loss in his right eye, which had occurred 2 weeks before, following push-up and sit-up exercise. The patient was found to have premacular haemorrhage associated with Valsalva retinopathy. Nd:YAG laser membrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…10 While most authors prefer to manage PMH ≤3DD size conservatively, some prefer to treat even the smaller hemorrhages. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Nd:YAG laser membranotomy is the simplest, quickest, most inexpensive, office-based procedure with a high success rate for the treatment of PMH. However, the technique has a few drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 While most authors prefer to manage PMH ≤3DD size conservatively, some prefer to treat even the smaller hemorrhages. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Nd:YAG laser membranotomy is the simplest, quickest, most inexpensive, office-based procedure with a high success rate for the treatment of PMH. However, the technique has a few drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it cannot be used in cases where the inferior margin of the blood collection lies near the fovea as the use of high energy close to the fovea can lead to macular hole, burn, and/ or scarring. [12][13][14][15][16] The only treatment option available for such patients is vitrectomy. However, surgery has its own risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…A macular hole associated with Valsalva retinopathy has been reported infrequently, to our knowledge. Elcin et al reported a spontaneously closed macular hole that developed after an uneventful Nd:YAG laser treatment in Valsalva retinopathy–induced premacular hemorrhage. The formation of macular hole in this case might be the result of the posterior vitreous detachment caused by a Valsalva maneuver and the associated traction at the vitreofoveal interface.…”
Section: Discussionmentioning
confidence: 99%
“…But in our patient, the location of ILM defect observed in the fundus after 7 weeks after the membranotomy was far from the inferior border of the initial sub-ILM hemorrhage, which may indicate that the laser performed at an inappropriate location. The explanation for the location of ILM defect far from the inferior border was due to the tangential traction of the ILM [25].…”
Section: Discussionmentioning
confidence: 99%